IMPLEMENTASI METODE DEMPSTER SHAFER DAN DESAIN BASIS DATA PADA SISTEM PAKAR DIAGNOSA PENYAKIT MATA - Diana, Diana (Universitas Bina Darma, 2017)
Limited knowledge of the patient against eye disease becomes a problem and make the patient difficult to predict the eye disease he suffered. In this case, the patient will need an expert who can early diagnose eye disease in order to prevent early. The existence of an expert system can be used as a consultation medium, where expert knowledge has been transferred into the computer system can be used as the basis by the expert system in answering user questions. The steps used are state assessment, knowledge acquisition and design. This research is focused on designing rule rules and database design. The Demspter Shaffer method is used for designing rule rules and relational database used as the database model. The results of this study is a database design on expert systems to diagnose eye disease. Keywords: Expert System, Shaffer Dempster Method, Database, Eye Disease